Narration and images: the use of the diary in the construction of the autobiographical narrative. Unpublished reflections from the work of Roland Barthes. - Faloni, Valentina (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The essay proposes a rereading of La camera chiara. Nota sulla fotografia in the light of the notes of the university course on the Preparazione del romanzo held by Roland Barthes in which the author investigates the process of transformation that goes from the biography to the Opera, from which the famous text originates. The investigation detects the correlation between narrative and images considering the diary and the narration of the self in the identity and professional construction as a tool and method of investigation and learning.